An in silico and in vitro approach for understanding CDK2 expression pattern and prognostic implications in breast cancer - Fatima Manhas; Shazia Sofi; Asma Jan; Nusrat Jan; Manzoor Ahmad Mir (Results in Chemistry)
Background: CDK2 (Cyclin-Dependent Kinase 2) is a Ser/Thr kinase that regulates cell cycle progression by promoting the G1/S transition and initiating DNA synthesis through its interaction with cyclins E and A. Unchecked cell growth, DNA damage, and protein deterioration are caused by an abnormally high level of CDK2. When it does so, it responds in excess, which triggers unchecked cell proliferation, which is what happens in breast cancer Objective: The study's primary objective is to explore CDK2's expression profile, functional role, and prognostic importance in the development of breast cancer Methods: In this study, we evaluated CDK2's expression profile, prognostic implications and interactions with other proteins to better understand how CDK2 influences the etiology of breast cancer. A range of computational techniques, including UALCAN, TIMER2.0, GEPIA, STRING, DISCO, ENRICHR, and Docking, were utilized Results: Breast cancer patients had highly regulated CDK2 levels. Utilizing cytohubba, the most significant 10 hub genes of the web were identified. The regulation of heterochromatin formation and cellular response to nitric acid are substantially enriched in the KEGG pathway analysis and gene ontology GO. Association with the p53 pathway was revealed by the KEGG pathway investigation. Adapalene strongly bound to protein CDK2 in a 3D schematic, with the lowest binding energy being −10.87 kcal/mol Conclusion: Collectively, the study shows that CDK2 promotes tumor growth and that blocking it in addition to conventional therapies will significantly enhance the medical outcomes of breast cancer patients.